Planar hybrid carbon-decorated zinc oxide nanowires for infrared photodetection - Ahmad, Harith; Thandavan, Tamil Many K. (Springer Verlag, 2018)
Vapor phase transport (VPT) assisted by thermal evaporation of methanol was utilized to favor the fabrication of hybrid carbon-decorated zinc oxide nanowires (C/ZnO NWs). The photoluminescence (PL) spectrum revealed evidence of optical properties for several defects such as zinc interstitials (Zni) and oxygen vacancy (Vo) in hybrid C/ZnO NWs. The PL also exhibited that the planar hybrid C/ZnO NWs photodetector has a wide range of sensitivity from ultraviolet (UV) to infrared (IR). The imaging results show formation of ZnO nanostructures which can be further confirmed from X-ray diffraction (XRD) results. XRD exhibits carbon (C)-related peaks at 12.88, 26, 43, 45, and 55° together with standard ZnO peaks. The incorporation of C shows excellent photoconduction towards varied laser powers (0.0, 7.82, 37.95, 69.20, 100.0, 130.0, and 160.0 mW) of IR illumination. The possibility of current drain in the device was evaluated based on the direct-current (DC) bias voltage of 0.00, 3.33, and 5.55 V. DC bias 3.33 and 5.55 V attributed increase of photocurrent towards the forward bias voltage. However, the reverse bias voltage illustrated a vast increase of photocurrent compared to the forward bias voltage. External quantum efficiency (EQE) at DC bias 5.55 V was 6.5–9.5 range folds greater than the EQE measured for zero bias voltage. Significant photoresponsivity was identical for various laser pulse ranging from 10 to 5000 Hz. Simultaneously, the rise (τr) and fall (τf) time were measured at 49 and 60.5 μs attributes that the fabrication technique can be improvised and implemented to enhance the efficiency of optoelectronic devices for future applications.